STRATEGY AND MANAGEMENT CONTROL SYSTEM IN A MANUFACTURING INDUSTRY IN SELECTED CITIES IN INDONESIA - Tubagus Ismail (Aceh International Journal of Social Science, 2015)
Abstract: The purpose of this study is to examine the relationship between strategy formation process and strategy implementation process with the usage of MCS. The focus of strategy formation process used in this study is intended strategy, emergent strategy, and implemented strategy. The focus of MCS used in this study, is interactive control system and diagnostic control system. This study uses structural equation modelling as multivariate analyses tool. AMOS software 16 program is used as the aid tool to solve the problem in SEM application. Respondents in this study are 287 upper managers who work in manufacturing industry with prospector typology strategy. The results from this study are: intended strategy positively and significantly influences the interactive control system; intended strategy positively and significantly influences the diagnostic control system; emergent strategy positively and significantly influences the interactive control system; and emergent strategy provides no influence on diagnostic control system; implemented strategy positively and significantly influences the interactive control system; implemented strategy positively and significantly influences the diagnostic control system. The strength of pressure that is used in each control system that will be able to provide optimal result has not known yet. The result of this study recommends that firms should have used many kinds of control usage which are suited with their condition.Keywords: intended, emergent, implemented, strategy, control system, manufacture